1991
DOI: 10.1111/j.1365-2710.1991.tb00281.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Β-2 Stimulation on Free Fatty Acids in Man

Abstract: In this study we present evidence that lipolysis in man is under beta-2 adrenergic control and that beta-2 stimulation produces a characteristic profile of individual free fatty acid (FFA) release. Twelve healthy volunteers received infusions of placebo (N Saline), terbutaline (a selective beta-2 agonist) and dilevalol (a new non-selective beta-blocker with beta-2 agonist activity). Plasma FFA concentrations during and after the infusions were measured using gas chromatography. A significant rise in total and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Several studies also mentioned that salbutamol may induce a significant increase in blood glucose concentrations and may possibly modify carbohydrates availability and utilization (Collomp et al., 2000a,b; Le Panse et al., ; Sanchez et al., ). It has been shown that β2‐agonists can induce a stimulation of hepatic glucose production and glucose release (Clutter et al., ), a stimulation of glycogenolysis and glycolysis with increased lactate and pyruvate release from tissues such as muscle (Rizza et al., ), a stimulation of lipolysis with increased glycerol and fatty acid release and lipid oxidation (Kendall et al., ; Schiffelers et al., ). Some studies reported no significant difference in total energy expenditure and substrate oxidation (based on gas exchange measurement during whole‐body exercise) following salbutamol administration, but the substrate oxidation balance might be modified during and after exercise (Collomp et al., 2000a,b, 2005; Arlettaz et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also mentioned that salbutamol may induce a significant increase in blood glucose concentrations and may possibly modify carbohydrates availability and utilization (Collomp et al., 2000a,b; Le Panse et al., ; Sanchez et al., ). It has been shown that β2‐agonists can induce a stimulation of hepatic glucose production and glucose release (Clutter et al., ), a stimulation of glycogenolysis and glycolysis with increased lactate and pyruvate release from tissues such as muscle (Rizza et al., ), a stimulation of lipolysis with increased glycerol and fatty acid release and lipid oxidation (Kendall et al., ; Schiffelers et al., ). Some studies reported no significant difference in total energy expenditure and substrate oxidation (based on gas exchange measurement during whole‐body exercise) following salbutamol administration, but the substrate oxidation balance might be modified during and after exercise (Collomp et al., 2000a,b, 2005; Arlettaz et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also mentioned that salbutamol may induce a significant increase in blood glucose concentrations and may possibly modify carbohydrates availability and utilization (Collomp et al, 2000a,b;Le Panse et al, 2007;Sanchez et al, 2012). It has been shown that β2-agonists can induce a stimulation of hepatic glucose production and glucose release (Clutter et al, 1980), a stimulation of glycogenolysis and glycolysis with increased lactate and pyruvate release from tissues such as muscle (Rizza et al, 1980), a stimulation of lipolysis with increased glycerol and fatty acid release and lipid oxidation (Kendall et al, 1991;Schiffelers et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…These important differences between carvedilol and metoprolol could have resulted from differential effects of these agents on peripheral lipolysis. The non‐selective β‐adrenergic receptor blocking activity of carvedilol might provide a more complete suppression of lipolysis given its ability to block both β 1 ‐ and β 2 ‐receptors [18,22,23]. The associated reduction in serum FFA could lower cardiac extraction of FFA since the uptake of FFA has been shown to be concentration dependent [24].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations in animal models of CHF suggest that β‐blockers may reduce myocardial utilization of free fatty acids. In humans with CHF, information concerning the impact of β‐blockers on energy substrate utilization and efficiency remains limited and, to some extent, contradictory [1618]. To date, no studies have compared the impact of different β‐blockers on these parameters in patients with CHF.…”
Section: Introductionmentioning
confidence: 99%
“…None of the mean changes in FFA concentration at 60 rnin were statistically significant but all were less than the values at 30 min. We and many others have shown previously that infusion of a 8-2 receptor agonist into human volunteers causes a rise in plasma FFA concentration (10,14,15). Terbutaline is a p-2 specific agent and attenuation of its effect on lipolysis by another agent thus indicates p-2 blocking activity.…”
Section: R E S U L T Smentioning
confidence: 89%